1994
DOI: 10.1111/j.1365-3148.1994.tb00252.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and epidemiological characteristics of hepatitis C in Scottish blood donors

Abstract: All blood donors in Scotland who were found to be infected with hepatitis C virus (HCV) in the first 6 months of routine testing of all donations for anti-HCV were contacted. Those who attended were counselled, a history of exposure to risk was sought, and blood was taken for alanine aminotransferase (ALT) level as a measure of liver function. The epidemiological features were then correlated with the virological findings and ALT. In the period under study between September 1991 and February 1992, 180,658 bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
14
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 17 publications
6
14
0
Order By: Relevance
“…We confirm that 1b is the most prevalent genotype among European donors [12]and patients [13], followed by 3a. We also found that IVDU and a history of blood transfusion are the main routes of HCV transmission, as observed in French studies [14, 15]and in other European countries [16, 17]. Genotype 1b seems to correlate with blood transfusion, and 1a and 3a strongly with IVDU [13, 18].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…We confirm that 1b is the most prevalent genotype among European donors [12]and patients [13], followed by 3a. We also found that IVDU and a history of blood transfusion are the main routes of HCV transmission, as observed in French studies [14, 15]and in other European countries [16, 17]. Genotype 1b seems to correlate with blood transfusion, and 1a and 3a strongly with IVDU [13, 18].…”
Section: Discussionsupporting
confidence: 81%
“…Those infected with genotypes 3a, and less often 1a, are more likely to have high ALT levels than those with other genotypes, as already observed [17]. …”
Section: Discussionsupporting
confidence: 68%
“…11 With only history of multiple sex partners present in 8.16% anti HCV positive cases sexual promiscuity was the other risk factor. A role for sexual transmission was suggested by studies of Crawford et al, 16 Luksamijarulkul et al, 20 and Brandao et al 22 The present study highlighted an important fact that exposure through minor percutaneous routes of transmission like tattooing and sharing of shaving kits or visit to road side barber along with multiple unsafe intravenous injections may have played an important role in HCV transmission in our blood donors. Therefore a need arises not only to routinely screen the blood donors for HCV but also to educate them about the modes of spread of this dangerous but preventable disease.…”
Section: Graph IIIsupporting
confidence: 61%
“…drug use present in 28.57% cases who gave a history of prolonged hospitalization or receiving multiple injections from quacks. IV drug use was found to be most common risk factor also by Crawford et al, 16 and Similarly Khattak et al 17 and Akhtar et al 18 revealed that positive donors had a history of past hospitalization or multiple injections.…”
Section: Graph IIImentioning
confidence: 82%
“…Low levels of infectivity in blood products and the absence of consistent symptoms in recipients may prevent the identification of other common–source outbreaks of HCV infection. Such unrecognised outbreaks may contribute to the 30–50% of HCV–infected individuals identified on screening with no obvious risk factors for infection [17, 18, 19]. …”
Section: Discussionmentioning
confidence: 99%